1971
DOI: 10.1039/tf9716700589
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the 2050 Å system of the nitric oxide dimer

Abstract: The far ultra-violet continuum of nitric oxide was assigned to the dimer by obtaining the following experimental evidence : (a) the intensity of the spectrum is proportional to; (b) the possibility that the carrier may be some other known oxide of nitrogen was eliminated ; (c) from the temperature dependence the enthalpy change accompanying dissociation was 2.24 (f 0.1) kcal/mol (100-140 K), in good agreement with 2.4 (f0.2) kcal/mol deduced from the dimer infra-red intensities ; ( d ) approximate upper and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

1972
1972
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(51 citation statements)
references
References 0 publications
2
49
0
Order By: Relevance
“…A very accurate restitution of the critical point is obtained using our new force field with deviations from experiments of 1.6% for the critical temperature, 3.2% for the critical pressure and 0.1% for the critical density. [33][34][35][36][37][38] and of some theoretical investigations [34,[39][40][41]. In the liquid state, this reaction has been studied by Smith et al [33] and Guedes [34] who reported equilibrium constants from 110 K to 170 K. The mole fraction of dimers in saturated liquid nitric oxide was found to vary from more than 90% at 110 K down to ~40% at 170 K. From these studies, it can be inferred that nitric oxide is strongly associated in the saturated liquid phase at low temperatures and that this degree of association decreases with increasing temperatures.…”
Section: Interaction Potential and Calculation Proceduresmentioning
confidence: 99%
“…A very accurate restitution of the critical point is obtained using our new force field with deviations from experiments of 1.6% for the critical temperature, 3.2% for the critical pressure and 0.1% for the critical density. [33][34][35][36][37][38] and of some theoretical investigations [34,[39][40][41]. In the liquid state, this reaction has been studied by Smith et al [33] and Guedes [34] who reported equilibrium constants from 110 K to 170 K. The mole fraction of dimers in saturated liquid nitric oxide was found to vary from more than 90% at 110 K down to ~40% at 170 K. From these studies, it can be inferred that nitric oxide is strongly associated in the saturated liquid phase at low temperatures and that this degree of association decreases with increasing temperatures.…”
Section: Interaction Potential and Calculation Proceduresmentioning
confidence: 99%
“…The binding energy of N2O with N0~ has been reported to be 0.2 eV [30] in which case the electron detachment would be exothermic on collision and it is well established that non-adiabatic processes readily occur in complexes [31]. Similar situations may apply to the other molecular species, e.g., the associative detachment NO" -(-NO = ONNO -I-e~ is 43 meV [32] exothermic but does not occur [1]. With the negative charge of NO" now known to be on the O atom, it is clear that the collision complex would have the form NONO" or NOON" rather than ONNO", a suggested explanation postulated previously [1].…”
Section: Resultsmentioning
confidence: 96%
“…In fact, the observed bond length is 2.180 Å in the solid phase [120] and 2.237 Å in the gas phase [121]. The dissociation energy is very low (1.6 kcal mol −1 ) [122]. The N-N atomic distances of nitrogen oxides support the importance of the geminal lone pairs relative to the vicinal lone pairs (Scheme 10).…”
Section: Nitrogen Oxidesmentioning
confidence: 91%